Mitigating Health Risks After Floods and Landslides in Nepal: A Public Health Perspective - Simkhada, Padam; Sathian, Brijesh; Simkhada, Bibha; van Teijlingen, Edwin; Koirala, Pragya (Nepal Journal of Epidemiology, 2024)
In summary, the current floods reveal the deeply seated public health vulnerabilities in this disaster-ridden region, and they are a grim reminder of the catastrophic impacts of climate change on our environment. Massively reducing the immediate risk of disease outbreaks requires immediate interventions. At the same time, longer-term strategies need to address the psychological and infrastructural wreckage. Through strengthening health systems, increasing community understanding and improving preparedness for disasters, Nepal can reduce the public health impact of future disasters and protect the well-being of its people.